Escuta psicológica clínica para os militares - Donegá, Márcio Rogério da Silva (Brasil, 2022)
This work proposes an investigation into the possibilities and difficulties of psychoanalytic listening in a militarized environment, starting from a look at the demand presented by the military institutions themselves to reduce suicide rates among their professionals. The characteristics that differentiate military institutions from civil ones are discussed, verifying how the appeal to maintain discipline is used to produce subjectivity and the almost permission to psychic suffering. The obstacle to the analyst's discourse as a counterpoint to the power to transform the other into an object, provided by the hierarchical structure in military institutions, is made from a psychoanalytic interpretation. The impossibility of psychoanalysis, the conflicts and the inventiveness of professionals who work in these institutions are seen both from an analysis of military regulations and the code of ethics of (the) professionals who work in these institutions. Finally, the reports of professionals, psychologists and psychologists who face the day to day in military institutions or received them in their clinics are presented.